Improving Worker Welfare Through Digital Innovation in BPJS Employment: Implementation Study and Its Impact - Miftahull Jannah Hasibuan; Dhira Kartika Amanda; Vina Claudia Sitompul; Salsabila; Tania Erlikasna Br Sinulingga; Kuperju Syahputra Ritonga; Rey Valdo Siahaan; Alde Tama Pasaribu; Jay Benhard Novrijal Sipayung (Contemporary Journal of Applied Sciences, 2024)
This research focuses on the implementation of digital innovation at BPJS Ketenagakerjaan as a strategic step to enhance workers' welfare in Indonesia. BPJS Ketenagakerjaan plays a crucial role in providing comprehensive social security through programs such as Old Age Security (JHT), Work Accident Security (JKK), Pension Security (JP), Job Loss Security (JKP), and Death Security (JKM). To improve service efficiency, transparency, and accessibility, BPJS Ketenagakerjaan introduced the Jamsostek Mobile (JMO) application, which allows participants to access information, file claims, and manage their memberships online. The study reveals that digital innovation via  JMO significantly impacts the ease of access to services and time efficiency for users. However, the implementation of digitalization also faces several challenges, including low digital literacy, limited technological infrastructure in remote areas, technical issues within the application features, and regulatory barriers that do not fully support digital transformation. Using a descriptive qualitative approach based on literature review, this research highlights the importance of enhancing digital education, strengthening technological infrastructure, and developing more inclusive application features. In conclusion, digital innovation at BPJS Ketenagakerjaan not only improves public service quality but also contributes to enhancing workers' welfare amidst evolving economic and social dynamics.